Male Homosexuality: Absence of Linkage to Microsatellite Markers at Xq28 - Rice, George; Anderson, Carol; Risch, Neil; Ebers, George (Science (American Association for the Advancement of Science), 1999)
Several lines of evidence have implicated genetic factors in homosexuality. The most compelling observation has been the report of genetic linkage of male homosexuality to microsatellite markers on the X chromosome. This observation warranted further study and confirmation. Sharing of alleles at position Xq28 was studied in 52 gay male sibling pairs from Canadian families. Four markers at Xq28 were analyzed (DXS1113, BGN, Factor 8, and DXS1108). Allele and haplotype sharing for these markers was not increased over expectation. These results do not support an X-linked gene underlying male homosexuality.